Transformation of the middle–upper ordovician sedimentary environment of the north China plate under the caledonian tectonic background: a case study of the ordovician majiagou formation in the qishan area - Zhao, Di; Wei, Xiang; Li, Rongxi; Zhao, Bangsheng; Wu, Xiaoli; Xia, Anquan; Feng, Kaixin (Frontiers in Earth Science, 2026)
This study documents an abrupt sedimentary and petrographic transition near the top of the Ordovician Majiagou Formation in the Qishan area, southwestern Ordos Basin, North China Plate. Detailed lithofacies analysis of two sections reveals a rapid shift from shallow-water platform mudstone and dolostone (with lamination and bioturbation) to deeper-water slope to base-of-slope deposits characterized by slump breccias and gravity-flow facies. Tuff/bentonite interlayers and widespread soft-sediment deformation indicate intensified syn-depositional disturbance during the late stage of Majiagou deposition. We interpret these observations as reflecting a major increase in accommodation and margin instability along the southern basin margin during late Ma VI time. However, because no new radiometric ages or geochemical fingerprints of arc-related volcanism are presented here, our tectonic discussion is framed as a sedimentological reinterpretation constrained by previously published age data rather than a direct chronological revision. Within this framework, the Qishan record suggests that tectonic influence related to Qinling Ocean subduction may have intensified by late Ma VI, potentially earlier than commonly inferred for the Pingliang stage. These results refine the depositional model for the Middle–Upper Ordovician transition and contribute to ongoing discussions of basin–orogen coupling along the southwestern margin of the Ordos Basin.